2014
DOI: 10.18632/oncotarget.2065
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor-temozolomide co-treatment inhibits melanoma growth through suppression of Chemokine (C-C motif) ligand 2-driven signals

Abstract: Target-specific agents used in melanoma are not curative, and chemokines are being implicated in drug-resistance to target-specific agents. Thus, the use of conventional agents in rationale combinations may result in optimization of therapy. Because histone deacetylases participate in tumor development and progression, the combination of the pan-inhibitor SAHA and temozolomide might provide a therapeutic advantage. Here, we show synergism between the two drugs in mutant BRAF cell lines, in association with dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
(59 reference statements)
1
21
0
2
Order By: Relevance
“…Therefore, combinations with classical chemotherapeutic agents [43, 44] or new small molecule inhibitors [45] are being investigated. According to our previous study, MPT0E028 also showed synergism in combination with tyrosine kinase inhibitors, such as erlotinib and sorafenib, in non-small cell lung cancer (NSCLC) and liver cancer, respectively [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, combinations with classical chemotherapeutic agents [43, 44] or new small molecule inhibitors [45] are being investigated. According to our previous study, MPT0E028 also showed synergism in combination with tyrosine kinase inhibitors, such as erlotinib and sorafenib, in non-small cell lung cancer (NSCLC) and liver cancer, respectively [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Most important epigenetic alterations are aberrant DNA methylation and histone modifications. [104][105][106] We conducted an analysis of genome-wide DNA methylation on endoscopic biopsies of dysplastic and malignant lesions to understand the role of epigenetic events associated with the progression of Barrett esophagus. We observed that the previously reported global hypomethylation phenomenon in cancer has its origins at the earliest stages of epithelial carcinogenesis and was seen in low grade dysplasia.…”
Section: Reflux Disease Barrett's Esophagus (Be) and Esophageal Adenmentioning
confidence: 99%
“…In melanoma, pan-HDAC inhibitors in combination with temozolomide have shown promise (19,20). For these reasons, we addressed the role of class I HDACs in melanoma and determined the molecular mechanism whereby these HDACs influence the response of melanomas to temozolomide.…”
Section: Introductionmentioning
confidence: 99%